Thyroid cancer : a clinical overview and a useful laboratory manual - Cantara, Silvia (Bentham Science Publishers, 2013)
This e-book provides a general overview on the clinical aspect of thyroid nodules and specific details on molecular characterization of the nodules. This e-book is particularly suitable for novice endocrinologists but laboratory biologists and technicians involved in the pre-surgical diagnosis of thyroid cancer can also benefit from the additional technical details offered in this text.